Hubungan Sikap Siswa dengan Perilaku Penerapan Memakai Masker, Mencuci Tangan, Menjaga Jarak, Menjauhi Kerumunan, dan Mengurangi Mobilisasi dalam Pencegahan Penularan Covid-19 - Atira Atira; Ayu Astuti; Dianto Dianto (Ide Insan Kreatif, 2023)
ABSTRACT Covid-19 in West Java ranks second in Indonesia with 709,602 cases, of which 693,921 cases recovered, and 14,761 died. In Cimahi City there were 13218 positive cases, 12820 recovered cases, and 239 dead cases. One of the triggers for the Covid-19 incident was due to a lack of implementing 5M behavior (wearing masks, washing hands, keeping distance, staying away from crowds, and reducing mobilization) in prevention transmission of Covid-19. Attitude is thought to be one of the determining factors in the behavior of implementing 5M. The purpose of this study was to determine the relationship between attitude and behavior in implementing 5M in preventing the transmission of Covid-19 at MTs (Madrasah and Tsyanawiyah) Pasundan Cimahi. The research method uses cross sectional analytic surveys. The sample size in this study was 73 respondents using the Total Sampling Technique. Data collection using a questionnaire. The results of the study were analyzed univariately and bivariately with the Chi-Square test. From 73 respondents, 64.4% of the respondents got a